HIV pre-exposure prophylaxis in transgender women: A subgroup analysis of the iPrEx trial - Deutsch, Madeline B. (Lancet HIV, 2015)
BACKGROUND: Oral emtricitabine-tenofovir disoproxil fumarate (FTC/TDF) pre-exposure prophylaxis (PrEP) is used to prevent the sexual acquisition of HIV. Transgender women (TGW) have unique characteristics that may relate to PrEP use, effectiveness, and safety. METHODS: The iPrEx trial was a randomized controlled trial (RCT) of oral FTC/TDF PrEP versus placebo among men who have sex with men (MSM) and TGW, followed by an open label extension (OLE). Drug concentrations were measured in blood by liquid chromatography and tandem mass spectroscopy. FINDINGS: Of the 2499 participants enrolled in the RCT, 29 (1%) identified as women, 296 (12%) identified as “trans”, 14 (1%) identified as men but reported use of feminizing hormones, such that 339 (14%) reported one or more of these characteristics (TGW). Compared with MSM, TGW more frequently reported transactional sex, receptive anal intercourse without a condom, or more than 5 partners in the past 3 months. Among TGW, there were 11 HIV infections in the active arm and 10 in the placebo arm, representing a hazard ratio of 1.1 (95% CI: 0.5 to 2.7). Among active arm participants, drug was detected in none of the TGW at the seroconversion visit, 18% (6/37) of seronegative TGW (P=0.31), and 52% (58/111) of seronegative MSM (P < 0.0001). PrEP use was not linked to behavioral indicators of HIV risk among TGW, while MSM at highest risk were more adherent. INTERPRETATION: There were no HIV infections among TGW having drug concentrations commensurate with use of 4 or more FTC/TDF tablets per week. TGW receiving PrEP had low drug concentrations, especially at times of potential HIV exposure, leading to no PrEP effectiveness among this subgroup. FUNDING: U.S. National Institutes of Health and the Bill and Melinda Gates Foundation; study medication was donated by Gilead Sciences.